Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) pada Pembentukan Nilai Karakter Siswa - Luthfi Emili Febrianti; Umil Muhsinin (Jurnal Pendidikan, Bahasa dan Budaya, 2025)
This study discusses the implementation of the Pancasila Student Profile Strengthening Project in shaping students' character at SD Negeri 082/IX Pijoan. The research employs a qualitative method with a descriptive approach, using observation, interviews, and documentation for data collection. The research subjects are sixth-grade students. The results indicate that the implementation of the Pancasila Student Profile Strengthening Project in character development involves three main stages: planning, implementation, and evaluation. The planning stage consists of forming a facilitator team, determining project themes and objectives, socializing the program, scheduling activities, developing teaching modules, and designing evaluation plans. The implementation stage follows the teaching modules developed by the facilitator team. The evaluation stage uses an assessment format during each meeting to monitor students' character development.